PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK - Yomance Nawipa; Lidya Kristina Tualena (Arfak Chem: Chemistry Education Journal, 2020)
AbstractUntil now, it is still necessary to change the learning model, because education in Indonesia still has problems with the low quality of education caused by the learning process that has not been effective. The purpose of this research is to know the effect of Problem Based Learning or what we usually know as problem-based learning on cognitive learning outcomes. This type of research is a quasi-experimental research design with Pretest-Posttest Nonequivalent Control Group Design. The population is students of class XI IPA which consists of two classes, namely XI IPA A and XI IPA B with a total of 44 students. Based on the results of the study, it was obtained that the hypothesis that the sig (2-tailed) result was 0.009 smaller than 0.025, it is said that the data hypothesis shows that H0 is rejected and H1 is accepted, that is, there is a significant difference in the cognitive learning outcomes of students in class XI IPA A with the use of the PBL model and class XI IPA B with the conventional model, with a percent effect of 17%. Keywords: Learning model, problem based learning, learning, cognitive